Semangat Kewirausahaan Dalam Etika Protestan Dan Manajemen Qolbu: Sebuah Perbandingan - Sulaiman Al-Kumayi (Ulumuna, 2006)
This paper will highlight the spirit of enterpreneurship in perspective of the Protestant Ethics (PE) and the Manajemen Qolbu (MQ) founded by K. H. Abdullah Gymnastiar, known as Aa Gym. Both are represenstative for Christian and Islam, respectively. PE—a thesis proposed by Max Weber—assumed a close correlation between the spirit of Protestantinism and the emerge of capitalism in Europe. Refering to this Weber’s thesis, I will examine the MQ in terms of its relation to the emerge of enterpreneurship among moslems in the Pondok Pesantren Daarut Tauhiid, Bandung, West Java. MQ is an icon and identically addressed to Aa Gym. He is known as an enterpreneur-preacher (dai-pebisnis) which is proved with his success in developing some bussines like MQTV, MQ Jernih, Al-Qur’an Selular, etc. This article is trying to explore further, some similarities and diversities between PE and MQ. And based on my research, the spirit of enterpreneurship established by Aa Gym has resemblance with the Protestant Ethics.